RIAS, ESTUARIES AND INCISED VALLEYS: IS A RIA AN ESTUARY? - Evans G.; Prego R. (My University, 2003)
Today, the term ria is rarely used by sedimentologists or stratigraphers, although it embodies all the characteristics of the so-called incised valleys - a topic of considerable interest since the increased understanding of the three dimensions of transgressive sequences using seismic stratigraphy. When it is used, it is usually referred to as a type of estuary; however, in many cases, only a minor part is influenced by estuarine processes. It is a useful term which should be revived as it encompasses in its entirety all the features and resulting deposits of an incised valley whether it is estuarine or marine.
Keywords: RIA; ESTUARY; INCISED VALLEY; TRANSGRESSION